2021
DOI: 10.1016/j.rmed.2021.106579
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for progressive fibrosis in patients with connective tissue disease associated interstitial lung diseases

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 48 publications
3
33
1
Order By: Relevance
“…ILD may be highly misdiagnosed or delay-diagnosed in patients with pSS, 3 although the progression of ILD is relatively less frequent in patients with pSS than other CTD. 33 The pSS patients who developed ILD exhibited increased morbidity and mortality, and required additional medical resources. Our data support that KL-6 is a valuable biomarker in identifying hidden ILD in patients with pSS.…”
Section: Discussionmentioning
confidence: 99%
“…ILD may be highly misdiagnosed or delay-diagnosed in patients with pSS, 3 although the progression of ILD is relatively less frequent in patients with pSS than other CTD. 33 The pSS patients who developed ILD exhibited increased morbidity and mortality, and required additional medical resources. Our data support that KL-6 is a valuable biomarker in identifying hidden ILD in patients with pSS.…”
Section: Discussionmentioning
confidence: 99%
“…However, PF-ILD other than IPF, such as idiopathic nonspecific interstitial pneumonia (iNSIP), fibrotic hypersensitivity pneumonitis (HP), connective tissue diseases (CTD)-ILD or autoimmune-ILD, also have a progressive phenotype, manifesting as a worsening of dyspnea, decline in lung function, and increased extent of fibrosis on high-resolution computed tomography (HRCT), with high morbidities, such as PVD. In Taiwan, we defined PF-ILD as developing any of the following within 2 years of diagnosis: (1) a relative decline in forced vital capacity (FVC) ≥ 10%; (2) a relative decline in diffusion capacity of carbon monoxide (DLCO) ≥ 15%; (3) worsening of radiological appearance or symptoms and a relative decline in FVC from 5~10% [ 1 , 2 ].…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, the PVD, in the late course of lupus with PF-ILD, was life-threatening [ 25 , 26 ]. In the recent Chiu et al study, they found that (20/150, 22%) with HCQ use and (17/150, 11.3%) with PAH in the 150 patients had ILD (33/150, 33% fibrotic predominant, PF-ILD) [ 2 ]. In this study, fibrosing CTD-ILD or IPF was grouped as fibrosing-ILD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this study, patients with two or more outpatient visits or one hospitalization for ILD (new ILD, ICD-9-CM codes 135, 237. (12)(13)(14). Patients aged ≥ 18 years with ILD and viral infection were included in the ILD cohort.…”
Section: Patient Enrollment and Sample Collectionmentioning
confidence: 99%